2018
DOI: 10.1016/j.jacc.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel Percutaneous Coronary Intervention in Patients With ST-Segment Elevation Myocardial Infarction With Cardiogenic Shock

Abstract: Of patients with STEMI and multivessel disease with cardiogenic shock, multivessel PCI was associated with a significantly lower risk of all-cause death and non-IRA repeat revascularization. Our data suggest that multivessel PCI for complete revascularization is a reasonable strategy to improve outcomes in patients with STEMI with cardiogenic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 25 publications
0
59
3
Order By: Relevance
“…The recent analysis from the KAMIR‐NIH (Korea Acute Myocardial Infarction‐National Institute of Health) registry examined CVI versus MVI in 659 patients with STEMI and CS. Contrary to the findings of CULPRIT‐SHOCK and our study, MVI was associated with lower mortality at 1 year (HR = 0.52, 95% CI: 0.38–0.73, P < 0.001) . However, there are a number of differences in study designs and definitions, which make interpretation and comparison difficult.…”
Section: Discussioncontrasting
confidence: 99%
“…The recent analysis from the KAMIR‐NIH (Korea Acute Myocardial Infarction‐National Institute of Health) registry examined CVI versus MVI in 659 patients with STEMI and CS. Contrary to the findings of CULPRIT‐SHOCK and our study, MVI was associated with lower mortality at 1 year (HR = 0.52, 95% CI: 0.38–0.73, P < 0.001) . However, there are a number of differences in study designs and definitions, which make interpretation and comparison difficult.…”
Section: Discussioncontrasting
confidence: 99%
“…Complete revascularization, which has recently shown to have better outcomes in hemodynamically stable AMI patients, is thought to be beneficial by improving both hemodynamics and ventricular function . MV‐PCI can also prevent early and late recurrent ischemia in non‐culprit lesions, improve perfusion to watershed areas, promote myocardial salvage and reduce infarct size . However, in our pooled analysis, we did not observe any reduction in short or long‐term mortality with MV‐PCI, compared to CL‐PCI.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast to CULPRIT‐SHOCK, recently published data from the KAMIR‐NIH registry study showed that MV‐PCI was associated with lower long‐term mortality and repeat revascularization, compared to CL‐PCI in AMI patients with CS . Direct comparisons between these two large studies should be made with caution, given differences in study design, population and inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations